ANTESEDEN DAN KONSEKUENSI DARI BRAND TRUST PADA PELANGGAN PUSAT KESEHATAN MASYARAKAT DI PAPANGGO II - Irena Paska (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
The background of this research refers to a previous study conducted by Kemp et al., (2012). Theobjectives of this research was to determine whether the Brand Trust has an influence on theAffective Commitment and Affective Commitment to Brand Advocacy on public health services.The design of this research applies primary data obtained by distributing questionnaires directlyto the 200 users of health services in a community health center in Jakarta. Data analysis used inthis research was Structural Equation Model (SEM). The results of this research conclude thatthere is a positive influence on Brand Trust Affective commitment. There is a positive influenceaffective commitment to Brand Advocacy.Keywords : Brand trust, Affective Commitment, Brand Advocacy